One-Pot Synthesis of 5-Acyl-2-amino-1,3,4-thiadiazoles - Lindström, Johan; Hallberg, Jesper (Synthesis, 2012)
A novel two-step one-pot synthesis of 5-acyl-2-amino-1,3,4-thiadiazoles by the reaction of acyl chlorides with N-isocyanoiminotriphenylphosphorane in the presence of KSCN is described. It was found that THF and KSCN are the key reagents to obtain the desired products in high isolated yields.
Keywords: acylation; heterocycles; cyclization; addition; ketones